Homo Islamicus and the Islamic economic system: implication on public policy - Mohd Yusop, Mohd Mahyudi (2015)
The identification of coherent decision-making behaviours depends upon the observed practices by society’s predominant economic agents. Interestingly, discourse on the Islamic economic system portrays the operations of homo Islamicus to manifest the perfect working of that ideal system. However, the approach taken is rather simplistic to the extent that the Islamic economic system is widely criticised as a mere utopian state for the present Muslim majority polities to create its semblance. This puts into question the viability of the Islamic economy idea while putting extra pressure for governments to cope with the high demands of contemporary identity politics. In view of the reported huge gap between theoretical construct and real activities, this paper challenges the presumption that homo Islamicus is dictating the way resources are allocated. Thus, this paper suggests a broad-based public policy to continuously transform the population of Muslim majority countries to be homo Islamicus.